Neuropsychiatric Adverse Events of Montelukast: An Analysis of Real-World Datasets and drug−gene Interaction Network - Umetsu, Ryogo; Tanaka, Mizuki; Nakayama, Yoko; Kato, Yamato; Ueda, Natsumi; Nishibata, Yuri; Hasegawa, Shiori; Matsumoto, Kiyoka; Takeyama, Noriaki; Iguchi, Kazuhiro; Tanaka, Hiroyuki; Hinoi, Eiichi; et al. (Frontiers in Pharmacology, 2021)
Montelukast is a selective leukotriene receptor antagonist that is widely used to treat bronchial asthma and nasal allergy. To clarify the association between montelukast and neuropsychiatric adverse events (AEs), we evaluated case reports recorded between January 2004 and December 2018 in the Food and Drug Administration Adverse Event Reporting System (FAERS). Furthermore, we elucidated the potential toxicological mechanisms of montelukast-associated neuropsychiatric AEs through functional enrichment analysis of human genes interacting with montelukast. The reporting odds ratios of suicidal ideation and depression in the system organ class of psychiatric disorders were 21.5 (95% confidence interval (CI): 20.3−22.9) and 8.2 (95% CI: 7.8−8.7), respectively. We explored 1,144 human genes that directly or indirectly interact with montelukast. The molecular complex detection (MCODE) plug-in of Cytoscape detected 14 clusters. Functional analysis indicated that several genes were significantly enriched in the biological processes of “neuroactive ligand–receptor interaction.” “Mood disorders” and “major depressive disorder” were significant disease terms related to montelukast. Our retrospective analysis based on the FAERS demonstrated a significant association between montelukast and neuropsychiatric AEs. Functional enrichment analysis of montelukast-associated genes related to neuropsychiatric symptoms warrant further research on the underlying pharmacological mechanisms